2013
DOI: 10.1038/ijo.2013.159
|View full text |Cite
|
Sign up to set email alerts
|

The snacking rat as model of human obesity: effects of a free-choice high-fat high-sugar diet on meal patterns

Abstract: We hereby show the importance of choice in the observation of fcHFHS diet-induced hyperphagia, which results in increases in meal number due to sugar drinking without any compensatory decrease in meal size. We thus provide a novel dietary model in rats that mimics important features of human overconsumption that have been ignored in rodent models of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
101
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 32 publications
15
101
2
3
Order By: Relevance
“…For example, mice fed a sugar solution showed increased expression of glucose transporters and cholecystokinin in ileum tissue compared to mice fed an equal amount of metabolizable energy via a solid sugar diet (Ritze et al 2014). In addition, we showed previously that fcHFHS-fed rats consume their dietary sugar component also during the light period (la Fleur et al 2014) and circadian disruption has been shown to induce insulin resistance (Shi et al 2013). This indicates that sugar drinking might affect insulin sensitivity indirectly.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, mice fed a sugar solution showed increased expression of glucose transporters and cholecystokinin in ileum tissue compared to mice fed an equal amount of metabolizable energy via a solid sugar diet (Ritze et al 2014). In addition, we showed previously that fcHFHS-fed rats consume their dietary sugar component also during the light period (la Fleur et al 2014) and circadian disruption has been shown to induce insulin resistance (Shi et al 2013). This indicates that sugar drinking might affect insulin sensitivity indirectly.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the night before the experiment palatable food items were removed to avoid direct interference of the fat and/or sugar consumption on insulin sensitivity. Lipid infusions have direct effects on insulin sensitivity (Lam et al 2003, Pereira et al 2014) and timing of sugar consumption is very different between animals on a fcHFHS and on a fcHS diet (la Fleur et al 2014). A further advantage of providing the animals with only a standardized amount of chow the night before the clamp is that all animals consumed a similar amount of calories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity was induced using a high-fat, high-carbohydrate choice diet (HFHC) in which both lard and palatable maltodextrin solution were available ad libitum in addition to chow, while control rats received chow only. This HFHC choice diet effectively models many physiological and behavioral aspects of diet-induced obesity, as rats gain weight rapidly through persistently increased intake, and develop peripheral leptin resistance, impaired glucose metabolism, and altered food motivation [23][24][25]. This diet is especially useful as a model of human diet-induced obesity because it combines the effects of food palatability and energy density with the stimulating effects of variety and choice.…”
Section: Introductionmentioning
confidence: 97%
“…While the rodent gastrointestinal anatomy and physiology differs significantly from that of human subjects (47) and rodent chow is not comparable with human diets in terms of form and composition (48) , rat and mice models can at least provide further clues into the understanding of how WG might impact on acute physiology or longerterm disease progression.…”
Section: Mechanistic Studies On Whole Grainsmentioning
confidence: 99%